The Influence of Project Based Learning Model to Students' Problem-Solving Abilities on The Material of Cubes and Blocks - Rahayu Ningsih, Sri Lestari; Agustinsa, Ringki; Rahimah, Dewi (JTMT: Journal Tadris Matematika, 2024)
This study aimed problem-solving abilities on cube and block lesson for eighth grade in SMP Negeri 8 Bengkulu City. This study was quasi-experimental research with The Nonequivalent Posttest Only Control Group Design. The population of this study was all eighth-grade students of SMP Negeri 8 Bengkulu City in academic year of 2022/2023. The samples of this study were students of class VIII-3 as the experimental class that used the Project Based Learning model and students of class VIII-4 as the control class that used a conventional learning method who were selected through purposive sampling. The instrument used in this study was a problem-solving ability test sheet. The results of hypothesis testing showed that the value > which was 2.751> 1.671. The results of this study indicated that there was an influence of the application of the Project Based Learning model on students' mathematical problem-solving abilities on cube and block lesson for eighth grade in SMP Negeri 8 Bengkulu City.